PERSPECTIVES OF NANOPOWDERS APPLICATION FOR MANUFACTURING OF MODIFYING ALLOYING COMPOSITIONS - A. Kalinichenko; A. Slutsky; V. Sheinert; N. Zyk; V. Borodulya; О. Rabinovich (Литьë и металлургия)
Application of nanomaterials for grain refining of metals and its allac is of great interest as it aimis achieveto higher physicalmechanical properties in finished parts. Analysis shows that to gain high effectiveness of nanoparticles it is important to provide proper input of these particles into alloying alloy. The aim of present research is study of initial nanoparticles structure on the base of titanium, boron, yttrium and carbon nanotubes as well as development of method to manufacture alloying alloys containing nanoparticles.Investigations of nanopowders phase compositions on the base of titanium, boron and yttrium have shown that active elements such as boron carbide, titanium carbide and nitride, yttrium oxide are base compounds of these nanopowders. Powder particles are formed by primary structural elements having mainly plate state (titanium and boron carbides) and containing equiaxial inclusions with sizes of 5–200 nm. Chemical composition of specimens synthesized is uniform and contains 98.0 – 99.5% of main compound.Results of metal-protector and nanoparticles mixing have revealed that the increase of mixing duration from 2 to 6 hours assist to more uniform elements distribution through the pellet volume. Applying extrusion method specimens of alloying alloys have been produced and elements distribution in cross-section and longitudinal directions were determined.Analysis of research implemented has shown that distribution of active nanopowders in matrix is more uniform in extruded alloying alloys specimens compared to ones produced by methods of sintering or pressing of powder mixtures.